Studi Kepustakaan Penerapan Terapi Kursi Kosong (Empty Chair) dalam Terapi Gestalt - Intan Prawitasari (Department of Islamic Guidance and Counseling, 2021)
The purpose of this study is to describe the empty chair technique in gestalt therapy regarding: 1) the successful application of the empty chair technique, 2) the goal and setting of the empty chair technique, 3) the procedure and duration of empty chair technique therapy, 4) suggestions and recommendations about the empty chair technique. The research method of applying the empty chair technique in gestalt therapy was library research. The 14 journals would be grouped and summarized into a table into 4 focus discussions. The main focus in Gestalt counseling is to help individuals through their transition from a state that is always assisted by the environment to a state of self-sufficiency (self-support).